Role of perpendicular to grain compression properties on the seismic behaviour of CLT walls. (February 2021) - Sandoli, A.; D'Ambra, C.; Ceraldi, C.; Calderoni, B.; Prota, A.
Abstract: In-plane seismic behaviour of Cross-Laminated Timber (CLT) walls is influenced by panel-to-panel and panel-to-foundation mechanical connections, which consist of hold-downs and angle brackets. Due to the platform constructional technology, the orthogonal to grain timber-to-timber contact is also involved in the seismic response of the panels. To date, literature theoretical approaches to evaluating the flexural load-bearing capacity of CLT panels focus their attention on the schematization of hold-downs and angle brackets only, under evaluating the role of timber compressed in the perpendicular direction. In this paper the influence of orthogonal to grain timber properties on the overall seismic behaviour of CLT walls has been investigated, proposing a general theoretical model to schematize the panel-to-panel and panel-to-foundation connections. A parabola-rectangle constitutive behaviour has been defined to describe the orthogonal to grain timber behaviour in the connection zones, while hold-downs and angle brackets are modelled adopting literature models. Five different failure conditions, described by mathematical formulations, able to describe the entire axial force-bending moment interaction domain have been defined. The proposed model has also been employed to schematize the connection zones in multi-storey CLT walls with openings, allowing to investigate the effect of the orthogonal to grain properties on its seismic behaviour. Results of nonlinear analyses demonstrate a significant influence of orthogonal to grain timber properties on seismic behaviour of the walls, affecting their strength, stiffness, ductility and collapse mechanisms. Highlights: The influence of the orthogonal to grain compression properties on seismic behaviour of CLT structures has been analysed. A theoretical model to schematize the connection has been developed, accounting for orthogonal to grain compression. Five different failure conditions describe the entire axial force-bending moment interaction domains of CLT panels. The model has been employed to schematize the mechanical connection in multi-storey CLT walls subjected to seismic actions. The importance of the orthogonal to grain compression effect on seismic behaviour of CLT walls has been highlighted.